Rural–Urban Differential in Health and Nutrition Day Implementation in Assam during Postpandemic Period - Tulika Goswami Mahanta; Nabanita Nirmolia; Abhijit Basu Biswas; Swarnali Devi Baruah (Journal of Public Health and Primary Care)
Background: Health and Nutrition Day was conceptualized by the National Health Mission to address the accessibility and utilization of integrated RCH and immunization services by the community. Subjects and Methods: Cross-sectional comparative study conducted covering all districts of Assam using MOHFW supportive supervision formats. Results: Number of sites monitored (342 urban and 1970 rural) were 2312. Headcount survey data were not available (9.8% of rural vs. 9.1% urban). ANM did not record the vaccination status of previous sessions in 5.7% of rural versus 1.5% of urban sites. Logistic availability was better in urban sites. Some sessions (3.9%) had open vials without date and time mentioned (4.4% rural vs. 3.9% urban was statistically significant). Open vial beyond 28 days was found in 3.2% of rural versus 0.6% in urban areas and were statistically significant. Key message was delivered better in urban areas. Conclusion: Noticeable disparity in the implementation of health and nutrition day more in favor of urban areas. Proper microplanning, uninterrupted supply chain, and capacity building with a focus on rural sites need to be prioritized.